Hierarchical CuCo2O4 nanobelts as a supercapacitor electrode with high areal and specific capacitance. (10th November 2015) - Vijayakumar, Subbukalai; Lee, Seong-Hun; Ryu, Kwang-Sun
Graphical abstract: Highlights: First time we report the synthesis of CuCo2 O4 nanobelts using hydrothermal method. The spinel CuCo2 O4 nanobelts exhibit maximum areal capacitance of 2.42 F cm −2 . After 1800 cycles, 127% of the initial specific capacitance was retained. Abstract: One dimensional hierarchical CuCo2 O4 nanobelt like architecture was synthesized via hydrothermal method. The synthesized nanomaterial was characterized using X-ray diffraction (XRD) analysis, field emission scanning electron microscopy (FESEM), and transmission electron microscopy (TEM). The TEM image clearly shows the nanobelt like architecture of CuCo2 O4 . The supercapacitor properties of CuCo2 O4 nanobelts electrode were tested using cyclic voltammetry, charge-discharge and electrochemical impedance spectroscopy. The spinel CuCo2 O4 nanobelts exhibit maximum areal and specific capacitance of 2.42 F cm −2 (809 F g −1 ). After 1800 continuous charge-discharge cycles, 127% of the initial capacitance was retained. This superior electrochemical supercapacitor property is mainly due to increased surface area and ion transport of nanobelt like architecture. The charge transfer resistance (Rct ) value of CuCo2 O4 nanobelt electrode is 3.85 Ω. This high capacitance and cyclic stability demonstrate that the prepared CuCo2 O4 nanobelts are a promising candidate for supercapacitors.